Sustained activation of 12/15 lipoxygenase (12/15 LOX) contributes to impaired renal recovery post ischemic injury in male SHR compared to females - Riyaz Mohamed; Jennifer C. Sullivan (BMC, 2023)
Abstract Background Acute kidney injury (AKI) due to ischemia-reperfusion (IR) is a serious and frequent complication in clinical settings, and mortality rates remain high. There are well established sex differences in renal IR, with males exhibiting greater injury following an ischemic insult compared to females. We recently reported that males have impaired renal recovery from ischemic injury vs. females. However, the mechanisms mediating sex differences in renal recovery from IR injury remain poorly understood. Elevated 12/15 lipoxygenase (LOX) activity has been reported to contribute to the progression of numerous kidney diseases. The goal of the current study was to test the hypothesis that enhanced activation of 12/15 LOX contributes to impaired recovery post-IR in males vs. females. Methods 13-week-old male and female spontaneously hypertensive rats (SHR) were randomized to sham or 30-minute warm bilateral IR surgery. Additional male and female SHR were randomized to treatment with vehicle or the specific 12/15 LOX inhibitor ML355 1 h prior to sham/IR surgery, and every other day following up to 7-days post-IR. Blood was collected from all rats 1-and 7-days post-IR. Kidneys were harvested 7-days post-IR and processed for biochemical, histological, and Western blot analysis. 12/15 LOX metabolites 12 and 15 HETE were measured in kidney samples by liquid chromatography-mass spectrometry (LC/MS). Results Male SHR exhibited delayed recovery of renal function post-IR vs. male sham and female IR rats. Delayed recovery in males was associated with activation of renal 12/15 LOX, increased renal 12-HETE, enhanced endoplasmic reticulum (ER) stress, lipid peroxidation, renal cell death and inflammation compared to females 7-days post-IR. Treatment of male SHR with ML355 lowered levels of 12-HETE and resulted in reduced renal lipid peroxidation, ER stress, tubular cell death and inflammation 7-days post-IR with enhanced recovery of renal function compared to vehicle-treated IR male rats. ML355 treatment did not alter IR-induced increases in plasma creatinine in females, however, tubular injury and cell death were attenuated in ML355 treated females compared to vehicle-treated rats 7 days post-IR. Conclusion Our data demonstrate that sustained activation 12/15 LOX contributes to impaired renal recovery post ischemic injury in male and female SHR, although males are more susceptible on this mechanism than females.